An update on newer pediatric supraglottic airways with recommendations for clinical use. Issue 4 (13th January 2015) - Jagannathan, Narasimhan; Ramsey, Melissa A.; White, Michelle C.; Sohn, Lisa; Bosenberg, Adrian
Summary Supraglottic airways are an established part of routine and emergency pediatric airway management, including use in difficult airways and neonatal resuscitation. With the introduction of newer supraglottic airways in children, efficacy can only be determined by comparing these devices with those that are already well established (laryngeal mask airway Classic and laryngeal mask airway ProSeal). This narrative review aims to present the current literature on these newer supraglottic airways and give recommendations for their use in various clinical scenarios based on the existing evidence.